åˆ©ç”¨å¯¹æ¯”æ•™å¦æ³•æé«˜å¤ç”¸ABDI AGAPE ä¸ä¸“å¦æ ¡äºŒå¹´çº§å¦ç”Ÿ å¦ä¹ åŠ©è¯â€”â€”â€œçš„â€ã€â€œå¾—â€ä¸Žâ€œåœ°â€çš„èƒ½åŠ› - Hidayati, Nur Fajrina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractLearning Chinese grammar can not be separated from learning Chinese vocabulary. In daily life, there are several commonly used words, such as noun, verb, and so on. Beside verb, noun, measure word, we have to learn particle. Particle is common used among sentences. The particles that we commonly see are "de", "de" and "de". Although the three particles do not have real meaning, but will affect the meaning of the sentence. The pronunciation of the three particles are same, so students often use them wrongly. The writer established the comparison method in SMK Abdi Agape Pontianak. After done three times of teaching process, the writer gave post-test to the students. According to the pre-test and post-test results found that the students to study "de", "de" and "de" of the statistical results of the analysis after research, more than 50% of students had been understood how to determine the usage of ?de?, ?de? and ?de?. Therefore, the writer ensure the comparison method will improve the students mastery in learning the particle ?de?, ?de?  and ?de?.Keywords: Particle,  Comparison  Method, ?de?, ?de? and ?de?